Los "roncadores " del género Pomadasys (Haemulopsis) [Pisces: Haemulidae] de la costa Pacífica de Centro América - López S., Myrna I. (1981)
The four species of eastern Pacific Pomadasys belonging to the subgenus Haemulopsis are analized and a description based on meristic and morphologic characteristics is given for each of the four species: P. leuciscus, P. elongatus, P. axillaris and P. nitidus. Juvenile as well as adult characters are included and species comparisons are made. P. corvinaeformis, the only Atlantic representative of the subgenus, is considered a cognate of the Pacific P. leuciscus. A key to Pacific Haemulopsis is included.